Comparison of Students’ Learning and Attitudes in Physical versus Virtual Manipulatives using Inquiry-Based Instruction - (:unkn) unknown (My University, 2021)
This research aimed to determine whether implementation of virtual technology or implementation of physical materials in a learning environment is more efficient in understanding physics concepts and developing positive attitudes at the high school level. The theory that framed this study is the model of learning as dynamic transfer. Participants were 96 ninth grade students (n = 96) distributed randomly to the virtual or physical group. Inquiry-based instruction continued during teaching of kinematics and dynamics, which lasted for eight weeks for both groups. Data from the Force and Motion Achievement Instrument (FMAI), student worksheets, the Attitude Towards Physics Scale (APCS), and anecdotal observations were collected. This study concluded that the use of physical and virtual manipulatives in inquiry-based instruction had the same effect on students’ conceptual and procedural knowledge, as well as their attitudes towards physics. However, students who dealt with physical experimentation had lower learning than their peers who experienced virtual experimentation due to measurement errors made by students. Furthermore, physical investigations left students with some irrelevant knowledge. Therefore, it is reasonable to assume that implementing virtual manipulatives is more advantageous for learning in some conditions. The final conclusion is that attitude and learning may be developed in a parallel manner.